2005
DOI: 10.1161/01.str.0000190097.08862.9a
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Evaluation of Embolic Trajectory in an Arterial Bifurcation

Abstract: Particles' distribution in a bifurcation is affected, beyond its outlets-flow-ratios, by the particle-to-branch diameter-ratio. The tendency of large particles to preferentially enter the wider bifurcation branch, beyond the flow ratio, is augmented under pulsatile flow conditions and is affected by particle-to-fluid density-ratio. These findings may have important implications for understanding the hemodynamic mechanisms underlying the trajectory of large emboli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 16 publications
2
39
1
1
Order By: Relevance
“…7,8 Fittingly, we did note sharper angulation of the ACA in comparison with that of the MCA in our study. However, these values did not differ between cases of ACAS and MCAS.…”
Section: Strokesupporting
confidence: 69%
See 1 more Smart Citation
“…7,8 Fittingly, we did note sharper angulation of the ACA in comparison with that of the MCA in our study. However, these values did not differ between cases of ACAS and MCAS.…”
Section: Strokesupporting
confidence: 69%
“…In vitro experimental models have highlighted the additional importance of the particle-tobranch diameter ratio in preferentially guiding the trajectory of larger emboli into wider bifurcation branches. [8][9][10] This notion could possibly explain the higher prevalence of atrial fibrillation, which is known to cause large emboli, observed in cases of territorial infarction of the MCA, which typically has the larger terminal ICA bifurcation branch diameter.…”
Section: Strokementioning
confidence: 99%
“…20,21 In Y-shaped bifurcations studied by Bushi et al, larger emboli were also found to exhibit a preference for wider branches. 22 Hemodynamics in the circle of Willis have been studied in glass models by Roach et al 23 and are the focus of a number of theoretical studies. 24 -28 However, we could find no reports of computational modeling of embolus trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…При изучении Y-образных бифуркаций D. Bushi и соавт. также обнаруживали крупные эмболы пре-имущественно в крупных ветвях [22]. M.R.…”
Section: ■ результатыunclassified
“…20 There is evidence that the rate of emboli flowing to the posterior circulation is lower even when normalized by the flow ratio. A recent study 23 has shown that the tendency of large particles is to preferentially enter into the wider bifurcation branch, in a higher proportion than the flow ratio, indicating it would be better to protect the larger arteries first.…”
Section: Protection Of the Posterior Circulationmentioning
confidence: 99%